Reconstruction of concrete morphology using deep learning - Ondřej Šperl; Jan Sýkora (Acta Polytechnica CTU Proceedings)
In this contribution, the concrete morphology is reconstructed with a simple algorithm selecting a pixel value based on the small set of surrounding pixels. A deep neural network (DNN) is used as a classifier, and the authors focus on studying different DNN architectures. The performance of the proposed algorithm is evaluated on several statistical descriptors and the grain size distribution curve.